2013
DOI: 10.1111/jpi.12034
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits matrix metalloproteinase‐9 activity by binding to its active site

Abstract: The zinc-dependent matrix metalloproteinases (MMPs) are key enzymes associated with extracellular matrix (ECM) remodeling; they play critical roles under both physiological and pathological conditions. MMP-9 activity is linked to many pathological processes, including rheumatoid arthritis, atherosclerosis, gastric ulcer, tumor growth, and cancer metastasis. Specific inhibition of MMP-9 activity may be a promising target for therapy for diseases characterized by dysregulated ECM turnover. Potent MMP-9 inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 52 publications
(50 reference statements)
7
79
0
Order By: Relevance
“…28 Previous studies have shown that melatonin inhibits MMP-9 activity via binding to its active site and via MT1 receptor signaling pathway. 41,42 Consequently, data obtained indicate that reduction in ECM deposition by melatonin could contribute to the alleviation of liver fibrosis, confirming results from rats treated with CCl 4 that were given gallic acid 43 or extracts from Acanthopanax koreanum. 44 Oxidative stress is one the most important stimuli to activate HSCs and plays a key role in the development of fibrosis.…”
Section: Discussionsupporting
confidence: 73%
“…28 Previous studies have shown that melatonin inhibits MMP-9 activity via binding to its active site and via MT1 receptor signaling pathway. 41,42 Consequently, data obtained indicate that reduction in ECM deposition by melatonin could contribute to the alleviation of liver fibrosis, confirming results from rats treated with CCl 4 that were given gallic acid 43 or extracts from Acanthopanax koreanum. 44 Oxidative stress is one the most important stimuli to activate HSCs and plays a key role in the development of fibrosis.…”
Section: Discussionsupporting
confidence: 73%
“…For example, melatonin has been shown to inhibit the expression and activity of MMP-2 and MMP-9 in both in vitro and in vivo models (32,39,41). A recent study has shown that melatonin inhibits MMP-9 by binding to its active site, which represents another possible mechanisms for the alteration in fibrosis during constant darkness (48). Melatonin has been show to diminish the secretion of TGF-␤ from hepatic stellate cells (25).…”
Section: Discussionmentioning
confidence: 97%
“…Melatonin induces apoptosis and reduces invasiveness of HepG2 cells in vitro through TIMP-1 upregulation and attenuation of MMP-9 activity via NFκB signal pathway [196] . Rudra et al [192] reported that melatonin reduces MMP-9 activity in AGS cell line and binds directly to its active site.…”
Section: Other Promising Dietary Antioxidantsmentioning
confidence: 99%
“…Melatonin is a naturally occurring antioxidant synthesized mainly by the pineal gland of vertebrates and also found in many edible plant products [191] . Recent research documents that consumption of tropical fruit enhances the serum melatonin level as well as raises the antioxidant capacity of blood serum [191,192] . Melatonin retards the development of cancer in different animal models and possesses strong anti-proliferative and proapoptotic effects in various cancer cells.…”
Section: Other Promising Dietary Antioxidantsmentioning
confidence: 99%